BEBERAPA ASPEK BIONOMIK ANOPHELES SP DI KABUPATEN SUMBA TENGAH, PROVINSI NUSA TENGGARA TIMUR - Adyana, Ni Wayan Dewi (Badan Penelitian dan Pengembangan Kesehatan, 2011)
Research Some Aspects of Anopheles sp Bionomik in Central Sumba Regency, Province of East Nusa Tenggara. Committed in the territory Maradesa Health Center. Data were collected by catching adult mosquitoes by using bait People inside and outside the home, a collection of breaks in the wall and at home, continued with larval surveys in all potential breeding places. The results showed that the biting behavior tends eksofagik found on An. kochi, An. aconitus and An.barbirostris with bite density peaks in An. aconitus (0.6 persons/hour) with a biting peak at 20:00 to 21:00. Behavior tends eksofilik break in An. kochi, An. aconitus, An. tesselatus, An. barbirostris, An. vagus, An.flavirostris, An. maculatus and An. indefinitus with the highest density in An.aconitus (0.9 persons/hour) at 1:00 a.m. to 2:00 a.m. Anopheles larvae breeding places found in the small hole in the ground, creek, wetland, non-permanent irrigation, water reservoirs in the vegetable garden, ditches, puddles, swamps, springs, with species that are found as An.kochi, An.aconitus, An. tesselatus, An. barbirostris, An. vagus, An. flavirostris, An. maculatus, An. indefinitus and An. annullaris